Study on the Mechanical Behavior of Double Primary Support of Soft Rock Tunnel under High Ground Stresses and Large Deformation - Zhe Liu (Advances in Civil Engineering)
Double primary support structures could effectively solve the problem of large deformation of surrounding rock for soft rock tunnels. However, the mechanical behavior of this new support structure is still incomplete, and the design method should be revised. Based on the theory of energy conversion, this paper analyzes the support characteristic curve of double primary support and puts forward the dynamic design method of double primary support. Considering that the secondary lining can be set after monitoring the deformation amount and deformation rate of the first primary support, its support parameters can be dynamically adjusted according to the actual situation. By applying the double primary support design method in the Maoxian tunnel of Chenglan Railway, the field monitoring results show that the double primary support has a significant effect on the energy release of surrounding rocks, greatly reducing the load acting on the secondary lining and ensuring the safety and reliability of the tunnel structure.